ANALISIS PENGARUH FINANCING TO DEPOSIT RATIO (FDR) TERHADAP PROFITABILITAS PERBANKANSYARIAH DI INDONESIA (Rasio Keuangan pada BUS dan UUS Periode 2008-2010) - Suryani, Suryani (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2012)
This study aimed to (1) analyze the condition of Financing to Deposit Ratio (FDR) of Islamic Banking in Indonesia; (2) analyze the profitability of sharia banking in Indonesia; and (3) to analyze the influence of Financing to Deposit Ratio (FDR) of the profitability of sharia banking in Indonesia. This study took samples at Islamic banks in Indonesia including 11 Islamic Banks (BUS), 23 Business Units of Sharia Banking (UUS). The research data is from Islamic Banking Statistics published by Bank Indonesia from January 2008 until December 2010 (Financial Ratio Study to BUS and UUS period 2008-2010). The number of Islamic banks used is 34 banks. The technique uses simple linear regression analysis with the help of the program EVIEWS version 5. The results of analysis is further illustrated as follows: First: Financing to Deposit Ratio (FDR) of sharia banking has an average of 103.65% during the year 2008, 89.70% in 2009 and 94.37% in 2010. Overall, the average Financing to Deposit Ratio (FDR) in the three years is about 98.79%. Second: Return on Asset (ROA) is one of the profitability ratio used to measure the effectiveness of the company in generating profit by leveraging its total asset. Based on the description of the variables, it shows the average Return on Asset (ROA) in 2008 is of 1.77%, 1.98% in 2009 and 1.74% in 2010. This result indicates that the average Return on Asset (ROA) in three years of observation is still above the prevailing bank. Third: The result of regression analysis indicates no significant of Financing to Deposit Ratio (FDR) for Return on Assets (ROA). The quantity t count is 0.475 far below the t table 2.032. The result of study differs from the study of Adi Stiawan (2009), but supports the study of Nurkhosidah Siti (2010) and Yuliani (2007). This study shows no significant effect on bank profitability.